Siege of Savannah
Regimental orderly book (1779 July 2-October 2) for the British Army, chiefly at Savannah, Ga., and regimental orderly book (1779 September 18-October l4) for the Continental Army at Savannah.
Collection material in English.
Keywords: Great Britain. -- Army -- Order-books.; United States. -- Continental Army -- Order-books.; Georgia -- History -- Revolution, 1775-1783.; Savannah (Ga.) -- History